Comparative leaf blade anatomy and micromorphology in the systematics and phylogeny of Bambusoideae (Poaceae: Poales) - Leandro, Thales D. [UNESP]; Scatena, Vera L. [UNESP]; Clark, Lynn G. (My University, 2020)
Leaf blade anatomical and micromorphological data have increasingly proved to be useful in the systematics and phylogeny of Bambusoideae. The presence of well-developed, asymmetrically strongly infolded mesophyll cells (arm cells) as seen in cross-section is regarded a synapomorphy for bamboos, whereas many well-known, widely used features for diagnosing groups remain to be formally tested in a comprehensive phylogenetic framework. In this review, we investigate the use of anatomical and micromorphological features in defining and delimiting minor and major groups in Bambusoideae. A general description of the leaf blade as seen in cross-section and surface view is provided for the subfamily, as well as features commonly found in the three currently recognized tribes (Arundinarieae, Bambuseae and Olyreae) and their subtribes. Some features, including midrib vasculature, fusoid cells and stomatal apparatus, are discussed in the light of systematic and phylogenetic perspectives, along with a clarification of terminology. Illustrations of relevant features are also provided. This review allowed us to elucidate anatomical and micromorphological features useful in defining and delimiting lineages but also to highlight some research priorities in Bambusoideae.
Keywords: Bamboos; Epidermis; Grass anatomy; Leaves; Mesophyll